The Irr1/Scc3 protein implicated in chromosome segregation in Saccharomyces cerevisiae has a dual nuclear-cytoplasmic localization. Issue 1 (December 2017) - Kowalec, Piotr; Fronk, Jan; Kurlandzka, Anna
Abstract Background Correct chromosome segregation depends on the sister chromatid cohesion complex. The essential, evolutionarily conserved regulatory protein Irr1/Scc3, is responsible for the complex loading onto DNA and for its removal. We found that, unexpectedly, Irr1 is present not only in the nucleus but also in the cytoplasm. Results We show that Irr1 protein is enriched in the cytoplasm upon arrest of yeast cells in G1 phase following nitrogen starvation, diauxic shift or α-factor action, and also during normal cell cycle. Despite the presence of numerous Crm1-dependent export signals, the cytoplasmic pool of Irr1 is not derived through export from the nucleus but instead is simply retained in the cytoplasm. Cytoplasmic Irr1 interacts with the Imi1 protein implicated in glutathione homeostasis and mitochondrial integrity. Conclusions Besides regulation of the sister chromatid cohesion complex in the nucleus Irr1 appears to have an additional role in the cytoplasm, possibly through interaction with the cytoplasmic protein Imi1.